What is the "digital divide" and why is it important? - Sparks, Colin (Javnost (Ljubljana), 2013)
This article begins with a consideration of the different meanings that have been given to the digital divide, and to the normative concerns that researchers have brought to its investigation. It then examines three major traditions of research into the subject: that which stresses issues of physical access; that which adds to the discussion of technical availability astress upon some of the cultural competences and skills necessary to utilise the technologies fully; and a third which examines situations in which technical availability is almost universal but in which social and cultural factors play a determinant role in the kinds of usage adopted. Building upon the existing state of knowledge, the article goes on to consider its implications both for future research and for the kinds of policies which might be adopted to address the problems of social inclusion today and in the future.
Keywords: informacijska tehnologija; information technology; komunikacijska tehnologija; digitalne komunikacije; sociologija komunikacij